Penerapan Teknologi Augmented Reality Catalog Digital Pot Bunga Berbasis Android - Fitrani, Arif Senja; Dhani, Bayu Rama (Indonesian Journal Publisher, 2024)
Home industry or is known home industry has many variations, one of which is flower pot, as a storage medium for plants, flower pot can also be used as decorations to beautify plants, flower pot sellers are now in great demand in Candiharjo residents. Candiharjo residents started to develop a business selling flower pot because the way to make them is very easy and has a lot of devotees. The background of interest in this research is based on the results of observations made with home industry sellers. In general, services for ordering or marketing media use brochures using photos without being able to explore in more detail, therefore a new service is needed so that they can display products in real time in 3 dimensions (3D) and can be interactive with buyers. The author's goal of conducting this research is to design an application so that Flower Pot buyers are interested in the products offered by sellers through digital catalogs using Augmented Reality (AR) technology and make it easier for buyers to visualize Flower Pot models interactively. The results of this study are the Augmented Reality Digital Catalog Application to provide an interactive visualization of the Flower Pot model in 3 dimensions using a 3D developer application.